Necessidades especiais de escolares com diabetes mellitus tipo 1 identificadas por familiares - Braga, Tania Moron Saes [UNESP]; Bomfim, Diogo Pazzini; Sabbag Filho, Daher (Associação Brasileira de Pesquisadores em Educação Especial - ABPEE, 2012)
Catering to students according to their various special needs is a challenge. As opposed to the field of disability, there is little research in Brazil on students with chronic diseases and their specific needs at school. The purpose of this study was to identify the special needs of children with diabetes mellitus type 1. The participants were 37 family members of students in treatment in an outpatient center at a state of São Paulo medical school. A semi-structured interview was carried, which was audio recorded and transcribed for analysis. The results showed that all participants informed the school informed about their child's condition, however 29,7% reported that inclusion or access to school was difficult, due to the teacher being uninformed about diabetes control, inadequate school lunches, and preconceptions of peers and school supervisor, or the student's embarrassment. Absenteeism occurred among 70,3% of the students, mainly due to doctor appointments. Special needs were identified by 32,4%, including meals, performance in school tasks and the need to better inform school professionals about the condition. Furthermore, 72,9% reported some kind of support to cope with diabetes had been provided, mainly by health professionals. In order to improve their child's development at school 51,3% presented suggestions such as including appropriate school meals, better preparation of school for dealing with diabetes, i.e. lectures and training for teachers. Our suggestion is that there should be a closer relationship between the school and health services, but the first step towards intersector integration is to identify the needs of students with chronic diseases, such as this study showed, by focusing on diabetes mellitus and its impact on the school.

É um desafio atender aos alunos, em suas diversas necessidades especiais. Diferentemente das deficiências, há poucas pesquisas no Brasil sobre estudantes com doenças crônicas e suas especificidades, na escola. O objetivo do presente estudo foi identificar as necessidades especiais de escolares com diabetes mellitus tipo 1. Participaram 37 familiares de escolares em tratamento ambulatorial de uma faculdade paulista, por meio de entrevista semiestruturada, gravada em áudio e transcrita para análise. Os resultados mostraram que todos comunicaram a escola a respeito da doença do filho, mas, mesmo assim, 29,7% relatam dificuldade de inclusão ou acesso à escola, como desconhecimento do professor para o controle do diabetes, merenda escolar inadequada, preconceito dos colegas e da diretora ou vergonha por parte do aluno. As faltas ocorrem com 70,3% dos alunos, principalmente devido às consultas médicas. Necessidades especiais foram identificadas por 32,4%, incluindo a alimentação, o desempenho escolar e a necessidade de profissionais da escola mais bem informados sobre a doença. Além disso, 72,9% referem algum tipo de apoio para enfrentar o diabetes, principalmente de profissionais de saúde. Dos familiares, 51,3% apresentam sugestões para um melhor desenvolvimento do filho na escola, incluindo alimentação escolar adequada e melhor preparo da escola para lidar com o diabetes, como palestras e treinamento aos professores. Sugerimos a aproximação entre a escola e a área da saúde, porém, o primeiro passo para a integração intersetorial é identificar as necessidades desses alunos com doenças crônicas, como foi possível com este trabalho, ao enfocar o diabetes mellitus e suas repercussões escolares.
Special needs of students with diabetes mellitus type 1 identified by relatives
Keywords: Educação Especial; Inclusão; Articulação saúde-educação; Desenvolvimento e aprendizagem; Special Education; Inclusion; Health needs; Development and learning